Patagonema iubatum gen. nov. and sp. nov. (Nematoda, Oncholaimidae, Octonchinae) from Patagonia sandy beach (Argentina) - Pastor, Catalina Teresa (2014)
Patagonema iubatum gen. nov. sp. nov. is described from a sandy beach at Playa Pozo, Golfo Nuevo, Argentina. It resembles Oncholaimidae (Nematoda: Enoplida) and it is characterized by a buccal cavity comprising a combination of three teeth and three mandibular ridges with small teeth. The new genus is also characterized by the presence of papillose pre-cloacal supplements, cephalated spicula and a gubernaculum with dorsal apophysis and lateral piece, and a new demanian system configuration. Patagonema iubatum sp. nov. has 9-11 papillae-like pre-cloacal supplements, short and cephalated spicula and a gubernaculum with dorsal apophysis and pointed lateral piece. Its position inside Oncholaimidae is discussed.